Evaluation of Fire Disaster Preparedness in Selected Universities in Osun State Nigeria: A Qualitative Study - Ngwoke, Nwora Valentine; Fayomi, Fidelis Olukayode; Wahab, Akeem Bolaji (NIU Journal of Humanities, 2024)
Buildings are susceptible to fire disasters all over the world, university buildings are frequently used by lots of students, staff and faculty members, this is in addition to the volume of combustible materials in the classes, offices, laboratories and students’ hostels. This makes the buildings prone to fire incidents. This study investigated fire disaster preparedness in selected university buildings in Osun state, Nigeria. The study assessed firefighting equipment and facilities, training/education of building users, awareness of fire disaster preparedness, availability of water for firefighting, supply of firefighting equipment and facilities, introduction of new technology and firefighting operations, evacuation drills for building users, availability of evacuation plans, fire doors, consideration of fire disaster preparedness during the design and post-construction stages of the buildings and factors influencing fire disaster preparedness. The research adopted the qualitative method, using in-depth interview (IDI) to collect data from 15 interviewees. Manual thematic analysis was used in analysing the data. Findings revealed that fire disaster preparedness was low in the selected university buildings in Osun state, Nigeria. The study concluded that there were inadequate firefighting equipment and facilities, unavailability of evacuation plans, inadequate training of building users, low awareness, lack of new technology and firefighting operations, lack of fire doors in the buildings. The study suggested that more firefighting equipment and facilities should be provided in the buildings, inclusion of fire doors and fire exit doors, evacuation plans in the buildings, increase awareness and training of users of buildings in universities, introduce new technology in firefighting operations. Keywords: Fire disaster preparedness, evacuation, interviewees, firefighting, thematic analysis